2010
DOI: 10.1086/650574
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Linezolid Is Mediated by thecfrGene in the First Report of an Outbreak of Linezolid‐ResistantStaphylococcus aureus

Abstract: We report the presence of the cfr gene underlying the resistance mechanism involved in a clinical outbreak of linezolid-resistant S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
161
3
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(180 citation statements)
references
References 22 publications
5
161
3
4
Order By: Relevance
“…Worse yet, the gene encoding this methylase is found on a transmissible plasmid, and recent outbreaks of linezolid resistance resulting from this mechanism in Madrid suggest that the era of almost universal susceptibility of S. aureus to linezolid may be coming to an end. 4 All of which brings us back to NDM-1. What makes this enzyme so frightening is not only its intrinsic ability to destroy most known beta-lactam antibiotics but also the company it keeps.…”
Section: Ndm-1 -A Cause For Worldwide Concernmentioning
confidence: 99%
“…Worse yet, the gene encoding this methylase is found on a transmissible plasmid, and recent outbreaks of linezolid resistance resulting from this mechanism in Madrid suggest that the era of almost universal susceptibility of S. aureus to linezolid may be coming to an end. 4 All of which brings us back to NDM-1. What makes this enzyme so frightening is not only its intrinsic ability to destroy most known beta-lactam antibiotics but also the company it keeps.…”
Section: Ndm-1 -A Cause For Worldwide Concernmentioning
confidence: 99%
“…3 However, the development of resistance due to the acquisition of the cfr gene increases concern because the cfr gene can be transferred to other strains and can spread in outbreaks, leading to important complications when providing therapy to infected patients. 5 In this report, we have demonstrated that linezolid-susceptible and -resistant MRSA belongs to the same clone, which leads us to conclude that the resistance gene was acquired during treatment. The appearance of resistance against clindamycin, chloramphenicol and linezolid initially suggested the presence of a cfr gene, and this finding was corroborated by PCR.…”
mentioning
confidence: 69%
“…[2][3][4] However, the first outbreak of a linezolid-resistant MRSA due to a different resistance mechanism has recently been described: the acquisition of cfr gene, which also confers chloramphenicol, 16C macrolides, streptogramin A and clindamycin resistance. 5 Previously the cfr gene was described in other staphylococcal species of animal origin. 6 Moreover, other cases of cfr-mediated linezolid resistance in S. aureus and S. epidermidis strains isolated from human infections have also been published.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the emergence of vancomycin-resistant S. aureus (VRSA) in 2002 in the United States [7] and the first outbreak of linezolid-resistant MRSA reported in 2008 [8] limits the use of these antibiotics. The resistance to these antibiotics is constantly increasing [9,10] hence, there is an urgent need for a new antimicrobial agent which will be effective to combat these multidrug-resistant bacteria.…”
mentioning
confidence: 99%